The Narrations on the Compilation of the Qur’an between Affirmation and Denial: An Analytical Study (Journal of Imam Al-Kadhim College, 2025)
This study explores the compilation of the Q This study explores the compilation of the Qur'an by analyzing the conflicting traditions between denial and affirmation, both in Sunni and Shi‘i sources, and examining relevant Qur'anic verses, rational proofs, and historical contexts.The research demonstrates that the Qur'an was indeed compiled during the Prophet Muhammad’s lifetime, including its preservation, ordering, and recording. Subsequent efforts under Abu Bakr and Uthman were documentation processes rather than acts of initial compilation. The study also dissects reports suggesting otherwise, critically addresses Orientalist claims, and reinterprets the role of Imam ‘Ali’s codex as an exegetical and chronological document rather than an alternative textur'an by analyzing the conflicting traditions between denial and affirmation, both in Sunni and Shi‘i sources, and examining relevant Qur'anic verses, rational proofs, and historical contexts.The research demonstrates that the Qur'an was indeed compiled during the Prophet Muhammad’s lifetime, including its preservation, ordering, and recording. Subsequent efforts under Abu Bakr and Uthman were documentation processes rather than acts of initial compilation. The study also dissects reports suggesting otherwise, critically addresses Orientalist claims, and reinterprets the role of Imam ‘Ali’s codex as an exegetical and chronological document rather than an alternative text.
Keywords: The Holy Qur’an; Compilation of the Qur’an; Narrations on Compilation; Qur’anic Documentation; Interpretive Narrations; The Holy Qur’an, Compilation of the Qur’an, Narrations on Compilation, Qur’anic Documentation, Interpretive Narrations.